Study the influence of the brake flaps on the ship braking and maneuvering using CFD - ديب , رهف; نوار عباس (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, brake flaps were added to the hull of the KVLCC2 ship, and their effect on increasing the braking force of the ship was studied to reduce the large distances traveled by large ships during the stopping operation and before reaching the final stopping stage. This study used a Computational Fluid Dynamics (CFD) technique. The RANS equations and k-ω SST model were used to solve the Navier Stocks Equations. The program ANSYS was used in this research. Initially, the numerical results were compared with the available experimental results. The agreement between both results was that good. After that, the calculations were made with one brake flab in several sites to the symmetrical part of the ship's hull, and then we added two flaps. The resistance and moments affecting the tanker during sailing were calculated at a straight course and different drift angles and speeds. The resistances and moments acting on the ship while sailing were calculated, and the results were studied and analyzed.